High-throughput virome profiling reveals complex viral diversity, co-infection patterns, and novel viruses in Cnidium officinale in Korea - Kang, Jeong-Hun; Lal, Aamir; Kwon, Minhyeok; Kwak, Myeonghwan; Jung, Chung Ryul; Kil, Eui-Joon (Frontiers in Plant Science, 2025)
High-throughput sequencing (HTS) was used to comprehensively profile the virome of Cnidium officinale Makino, an economically and medicinally important herb widely cultivated in Korea. Symptomatic leaf samples from nine major cultivation regions were pooled for sequencing. The analysis detected a diverse assemblage of viruses comprising 31 distinct species, including apple stem grooving virus (ASGV), cucumber mosaic virus (CMV), cnidium vein yellowing virus-1 (CnVYV-1), and cnidium virus X (CnVX). Importantly, four novel viral agents were identified: Cnidium officinale virus 1 (CnoV1), cnidium virus Y (CnVY), cnidium virus Z (CnVZ), and a unique cnidium virus–associated satellite RNA (satCnV). Viral read distributions varied markedly by regions; for example, CMV dominated in Bonghwa (two sites) and Geochang, while CnVY prevailed in Samcheok-B and Jecheon. Phylogenetic analyses of ASGV and CMV isolates from C. officinale revealed distinct lineages unique to this host, suggesting host-specific adaptation. Co-infection patterns indicated notable interspecific viral interactions. In particular, we observed a strong antagonism between CnVY and CMV, suggesting competitive exclusion or mutual suppression. A virus co-occurrence network analysis identified additional significant virus–virus associations, and principal component analysis (PCA) of virome profiles showed that samples cluster according to their dominant viruses. Overall, our findings emphasize the power of HTS in uncovering complex viromes and advancing understanding of virus ecology in clonally propagated medicinal crops. The comprehensive virome dataset generated here provides an essential foundation for future epidemiological studies and management strategies in C. officinale and related species.